Propane/propylene separation by adsorption using shaped copper trimesate MOF - M. G. Plaza (2012)
The separation of propane and propylene mixtures is generally carried out through an energy intensive distillation. Adsorption processes, such as PSA or SMB, present scope for energy savings and copper trimesate (Cu-BTC) MOF has been pointed out as a promising adsorbent to carry out this separation. However, MOFs need to be shaped prior to their use in packed bed adsorbers in order to reduce pressure drop, and the production of mechanically resistant shaped bodies reduces their adsorption performance. In this work, Cu-BTC tablets provided by BASF are evaluated to carry out propane/propylene separation by adsorption. The adsorption capacity of pure propane, propylene and isobutane was assessed in a magnetic suspension balance between 323 and 373 K up to 500 kPa. The evaluated material presents higher adsorption capacity than previously studied shaped samples, with a propylene adsorption capacity up to 6.6 mol kg(-1) at 500 kPa and 323 K. Fixed-bed desorption experiments in helium flow pointed out the presence of two adsorption sites for propane, propylene and isobutane. Cu-BTC tablets present selectivity for propylene over propane, with a separation factor of 2-3 at 373 K and pressures of 150-250 kPa, being able to separate binary mixtures representative of the outlets of a C3 splitter, thus showing to be promising for PSA operation. Finally it was confirmed that isobutane can displace and be displaced by a binary mixture of propane and propylene, showing a good candidate as desorbent in SMB operation using Cu-BTC tablets as adsorbent.